2020
DOI: 10.3390/jof6040359
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Isaria fumosorosea Spores by Steinernema feltiae and Heterorhabditis bacteriophora

Abstract: Entomopathogenic nematodes and fungi are globally distributed soil organisms that are frequently used as bioagents in biological control and integrated pest management. Many studies have demonstrated that the combination of biocontrol agents can increase their efficacy against target hosts. In our study, we focused on another potential benefit of the synergy of two species of nematodes, Steinernema feltiae and Heterorhabditis bacteriophora, and the fungus Isaria fumosorosea. According to our hypothesis, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Debilitated EPF-infected insects respire more, attracting EPNs that follow a path of CO 2 toward their hosts [ 52 , 106 ]. Steinernema feltiae and H. bacteriophora have been reported to disperse conidia and blastospores of Isaria fumosorosea in agar dishes and soil, suggesting a high ability for EPNs to spread EPF conidia in the shared environment [ 117 ]. These mechanisms of interaction can lead EPF and EPNs to generate a stronger effect than the sum of their individual effects [ 49 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Debilitated EPF-infected insects respire more, attracting EPNs that follow a path of CO 2 toward their hosts [ 52 , 106 ]. Steinernema feltiae and H. bacteriophora have been reported to disperse conidia and blastospores of Isaria fumosorosea in agar dishes and soil, suggesting a high ability for EPNs to spread EPF conidia in the shared environment [ 117 ]. These mechanisms of interaction can lead EPF and EPNs to generate a stronger effect than the sum of their individual effects [ 49 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nermuť et al [ 63 ] studied the potential of infective juveniles of entomopathogenic nematodes in the transmission of spores of C. fumosorosea . The authors assessed the dispersal of both the conidia and blastospores of C. fumosorosea by entomopathogenic nematodes S. feltiae and H. bacteriophora .…”
Section: Interactions Of Epn and Epf In Biocontrolmentioning
confidence: 99%
“…The authors concluded that although some EPN species are able to invade and kill bulb mites, their efficacy is in general quite low and they do not seem to represent a viable option for bulb mite biocontrol as a standalone approach [31]. EPNs have, however, other important functions in soil as they can disseminate fungal spores [70], serve as prey for invertebrate predators including mites and springtails or as a host for nematode-trapping fungi, such as Orbilia oligospora (Fresen.) Baral and E. Weber, Monacrosporium eudermatum (Drechsler) Subram.…”
Section: Entomopathogenic Nematodesmentioning
confidence: 99%